Impact of ICTs on Open and Distance Learning in a Developing Country Setting: The Philippine experience - dela Pena-Bandalaria, Melinda (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2007)
The influence of the information and communication technologies (ICTs) in open and distance learning (ODL) in a developing country, the Philippines, is critically evaluated in this paper. Specifically, this paper examines how ICTs have influenced or shaped the development of ODL in this country. Also examined are the different stages or generations of distance education (DE) in the Philippines, which are characterized mainly by the dominant technology used for the delivery of instructional content and student support services. The different ICTs being used in ODL and their specific applications to the various facets of this mode of delivery are also described. Also included is an examination on how quality of education is ensured in a technology-driven system of teaching and learning, which includes, among others, the employment of the ‘quality circle approach’ in the development of courses and learning packages, and the provision of appropriate technologies to perform academic processes and achieve institutional goals. Experiences of the various universities in the Philippines are also cited in this paper. Lessons have been drawn from the ODL experience to guide educators from other developing countries.